2017
DOI: 10.1111/cas.13233
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing deciphers a germline MET mutation in familial epidermal growth factor receptor‐mutant lung cancer

Abstract: Lung cancer accompanied by somatic activating mutations in the epidermal growth factor receptor (EGFR) gene, which is associated with a significant clinical response to the targeted therapy, is frequently found in never‐smoking Asian women with adenocarcinoma. Although this implies genetic factors underlying the carcinogenesis, the etiology remains unclear. To gain insight into the pathogenic mechanisms, we sequenced the exomes in the peripheral‐blood DNA from six siblings, four affected and two unaffected sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…A nephew had non-Hodgkin’s lymphoma at 12 (germline V843I negative). A healthy daughter carried germline V843I mutation.Ohtsuka, et al 2011 [46]1713MotherF70AsianUKADCL858R1813BrotherM41AsianUKADCL858R EGFR p.V834 L1914ProbandF57SurinamSADCL858RA daughter carried germline V834 L; Father died of massive hemoptysis of unknown cause.Van der Leest, et al 2018 [47]2014BrotherM57SurinamSNSCLCL858R2114SisterF46SurinamNSNSCLCL858R2214DaughterF42SurinamNSNSCLCL858R HER2 p.G660D2315ProbandF44AsianLSMulti-ADCsWTHER2 Family history of lung cancers among multiple maternal members; Daughter with germline G660D, and CT showed multiple GGNs in bilateral lungs at 30 (light smoker).Yamamoto, et al 2014 [48]2415MotherF74AsianNSMulti-ADCsWT MET p.N375K2516ProbandF75AsianNSADCL858RAnother sister (never-smoker) clinically diagnosed with lung cancer at 80.Tode, et al 2017 [49]2616SisterF63AsianNSADC19del2716SisterF63AsianLSADC…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nephew had non-Hodgkin’s lymphoma at 12 (germline V843I negative). A healthy daughter carried germline V843I mutation.Ohtsuka, et al 2011 [46]1713MotherF70AsianUKADCL858R1813BrotherM41AsianUKADCL858R EGFR p.V834 L1914ProbandF57SurinamSADCL858RA daughter carried germline V834 L; Father died of massive hemoptysis of unknown cause.Van der Leest, et al 2018 [47]2014BrotherM57SurinamSNSCLCL858R2114SisterF46SurinamNSNSCLCL858R2214DaughterF42SurinamNSNSCLCL858R HER2 p.G660D2315ProbandF44AsianLSMulti-ADCsWTHER2 Family history of lung cancers among multiple maternal members; Daughter with germline G660D, and CT showed multiple GGNs in bilateral lungs at 30 (light smoker).Yamamoto, et al 2014 [48]2415MotherF74AsianNSMulti-ADCsWT MET p.N375K2516ProbandF75AsianNSADCL858RAnother sister (never-smoker) clinically diagnosed with lung cancer at 80.Tode, et al 2017 [49]2616SisterF63AsianNSADC19del2716SisterF63AsianLSADC…”
Section: Resultsmentioning
confidence: 99%
“…Their mutant proteins are more stable than the wild-type and possess an oncogenic potential by activating Akt and p38 , thus facilitating cell growth and survival [48]. MET and EGFR are mutual complements, which activate the PI3K-AKT pathway by interacting with ERBB3; therefore, the inactivation of MET by its heterozygous germline mutation could complementarily enhance the EGFR-ERBB3-PI3K axis [49]. The oncogenic stress may explain the pathogenesis of EGFR mutation in lung cancer [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14 Asn375 to Lys375 replacement in MET reduced the affinity to HGF. 16 Taking these findings together, α-helix-367-375 may play a role in the association with HGF; thus, a change in orientation and/ or position of α-helix-367-375 might affect interactions between MET and HGF.…”
Section: Extracellular Domains Of Met-wt (Met-ecd-wt) and Met-v370dmentioning
confidence: 99%
“…Studies based on HGF binding, molecular modeling, and apoptosis induced by MET inhibitors indicated that the N375S mutation conferred mild resistance to MET inhibition . Recently, the N375K mutation was identified in four siblings affected by epidermal growth factor receptor (EGFR)‐mutant lung adenocarcinomas . Thus, N375 is a “hotspot” for mutations and may play an important role in the normal functions of MET receptor.…”
Section: Introductionmentioning
confidence: 99%